MED12 somatic mutations encompassing exon 2 associated with benign breast fibroadenomas and not breast carcinoma in Indian women. Issue 1 (19th September 2018) - Darooei, Mina; Khan, Fazal; Rehan, Mohd; Zubeda, Syeda; Jeyashanker, Erukambattu; Annapurna, Srirambhatla; Shah, Ashwin; Maddali, Srinivas; Hasan, Qurratulain
Abstract: Fibroadenoma is the most common type of benign breast tumor, accounting for 90% of benign lesions in India. Somatic mutations in the mediator complex subunit 12 ( MED12 ) gene play a critical role in fibroepithelial tumorigenesis. The current study evaluated the hotspot region encompassing exon 2 of the MED12 gene, in benign and malignant breast tumor tissue from women who presented for breast lump evaluation. A total of 100 (80 fibroadenoma and 20 breast cancer) samples were analyzed by polymerase chain reaction‐Sanger sequencing. Sequence variant analysis showed that 68.75% of nucleotide changes were found in exon 2 and the remaining in the adjacent intron 1. Codon 44 was implicated as a hotspot mutation in benign tumors, and 86.36% of the identified mutations involved this codon. An in silico functional analysis of missense mutations using consensus scoring sorting intolerant from tolerant (SIFT), SIFT seq, Polyphen2, Mutation Assessor, SIFT transFIC, Polyphen2 transFIC, Mutation Assesor transFIC, I‐Mutant, DUET, PON‐PS, SNAP2, and protein variation effect analyzer] revealed that apart from variants involving codon 44 (G44S; G44H), others like V41A and E55D were also predicted to be deleterious. Most of the missense mutations appeared in the loop region of the MED12 protein, which is expected to affect its functional interaction with cyclin C–CDK8/CDK19, causing loss of mediator‐associated cyclin depended kinase (CDK) activity. These results suggest a key role of MED12 somatic variations in the pathogenesis of fibroadenoma. For the first time, it was demonstrated that MED12 sequence variations are present in benign breast tumors in the south Indian population. Abstract : Fibroadenoma (FA) is the most common tumor, and somatic mutations in mediator complex subunit 12 (MED12) are critical for fibroepithelial tumorigenesis. The current study showed MED12 exon 2 mutations in 40% of patients with FA, >85% involving the codon 44 region. Different in silico tools predicted that G44H, V41A, and E55D are damaging to the MED12 protein and concentrated in the highly interactive loop region.